Can surgery relieve pain and act as first-line treatment for a large metastasis of the sternum?. (2019) - Manfredini, Beatrice; Morandi, Uliano; De Santis, Giorgio; Catani, Fabio; Stefani, Alessandro; Pinelli, Massimo; Baccarani, Alessio; Starnoni, Marta; Artioli, Fabrizio; Aramini, Beatrice
Highlights: Renal cell carcinoma (RCC) is the most frequent type of renal tumor in adults. RCC is able to metastasize through the blood system and lymphatic system. Metastases from RCC to the bones are often of the osteolytic type. The sternal metastatic site for RCC is a rare site and it often begins as pain. Abstract: Background: There are few papers published on sternal metastasis from renal cell carcinoma. The unifying element is the operability of the sternal metastasis if it is the only site of metastasis, on the operability of the primary site of the tumor and on the patient's health conditions. Presentation of the case: We present a case of a 66-years-old man undergone sternal resection for a large painful metastasis. He was previously undergone left nephrectomy for clear cells carcinoma. En bloc resection of the sternal manubrium and right clavicle was performed, a Gore-Tex mesh was placed. Histology confirmed metastasis of kidney clear cells carcinoma. Patient was discharged with no complications and no pain. Chest CT at six months follow up was negative for recurrence. Discussion and conclusion: We highlighted the importance of surgery as possible first-line treatment in symptomatic large sternum metastasis. Therefore, prospective studies should be considered to confirm our strategy.